Fatwa Qualification between Individual Training and Institutional Formation; An Applied Theory Study: التأهيل الإفتائي بين التكوين الفردي والتكوين المؤسسي دراسة نظرية تطبيقية - Abdelhamid Elshal, Amr; Sabry Elattar, Omair (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
يظل "المفتي" هو حجر الزاوية في العملية الإفتائية برمتها؛ حيث يقع على عاتقه عبء ومسئولية القيام بهذه المهمة الخطيرة والعظيمة؛ حيث هي في حقيقة الأمر إبلاغ عن الله مراده وأحكامه وتوقيع عنه. ونظرًا لإدراك أهل العلم خطورة منصب الفتوى وأهميته، فقد وضعوا مجموعة من الشروط والصفات التي ينبغي أن تتحقق فيمن يتصدر لهذه المهمة العظيمة والمسئولية الجسيمة، فتحدثوا عن عملية التأهيل والتكوين العلمي اللازم توافرها في المفتي وهذا ما يتناوله هذا البحث؛ حيث يتناول عملية التأهيل العلمي والبناء المعرفي للمتصدر للفتوى وفق مستويين: مستوى التكوين الذاتي والفردي. مستوى المؤسسات والهيئات والمراكز الإفتائية: والتي يقع على عاتقها القيام بمهمة التهيئة والتأهيل وفق واقع متشابك ومتداخل وتطور علمي ومعرفي كبير. وقد راعينا في هذا البحث طرح مقترح لخطة عملية تطبيقية يمكن للمؤسسات والهيئات العلمية المعنية بالفتوى وشئونها الاسترشاد بها وتطبيقها بحيث تحصل الثمرة المرجوة، وهي تكوين ذلك المفتي العصري المدرك لشانه العالم بزمانه. الكلمات المفاتيح: الإفتاء، التأهيل الإفتائي، التكوين المؤسسي، المؤسسات الإفتائية Abstract The Mufti remains the cornerstone of the entire fatwa process; wherein he shall bear the burden and responsibility of carrying out this grave and great task; where, in fact, it is to inform about God's will and provisions and to sign on Him. Because the scholars are aware of the seriousness and importance of the fatwa position, they have set a set of conditions and qualities that should be fulfilled by those who take the lead in this great task and grave responsibility. It deals with the process of scientific qualification and knowledge building for the issuer of the fatwa according to two levels;level of self and individual formation, and the level of institutions, bodies and fatwa centers: which are responsible for carrying out the task of preparation and rehabilitation according to an intertwined reality and a great scientific and cognitive development. We have taken into account in this research a proposal for an applied practical plan that the institutions and scientific bodies concerned with the fatwa and its affairs can be guided by and apply so that the desired fruit will be obtained, which is the formation of that modern mufti who is aware of the importance of the world in his time. Keywords: Ifta, fatwa qualification, institutional formation, fatwa institutions.